Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.4 - Adding, Subtracting, and Dividing Radical Expressions - Exercise Set - Page 538: 18



Work Step by Step

Simplify each radical to obtain: $=3\sqrt[3]{8(3)} + \sqrt[3]{27(3)} \\=3\sqrt[3]{2^3(3)} + \sqrt[3]{3^3(3)} \\=3(2)\sqrt[3]{3} + 3\sqrt[3]{3} \\=6\sqrt[3]{3} + 3\sqrt[3]{3}$ RECALL: The distributive property states that for any real numbers a, b, and c: (1) $ac + bc = (a+b)c$ (2) $ac-bc=(a-b)c$ Use the rule (1) above to combine like terms and obtain: $=(6+3)\sqrt[3]{3} \\=9\sqrt[3]{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.